Development of Biology Learning Media based on Echinoderm Diversity for Support Environmental Sustainability - R. Teti Rostikawati; Lufty Hari Susanto; Ilmi Zajuli Ichsan; Giry Marhento (Postgraduate, University of Mataram, 2023)
Biodiversity was the important topic for biology learning to support environmental sustainability, especially in Echinoderms biodiversity. The purpose of this study was to identify Echinoderm species found on Pangumbahan Beach, Ujung Genteng, Sukabumi and develop e-booklet teaching materials for students. The research procedure is field observation with the exploration of transect methods at 3 stations representing 3 ecosystems, namely rocky sand ecosystems, coral ecosystems, and seagrass meadow ecosystems. Sampling was carried out by transecting a combination of plots with a plot size of 5 x 25 meters at three different stations and the develop the learning media with research and development method. The results of the study found 3 classes, 4 orders, 4 families, and 4 genera of Echinodermata consisting of 7 species, namely Ophiocoma scolopendrina, Ophiocoma erinaceus, Ophiomastix annulosus, Diadema setosum, Tripneustes gratilla, Synapta maculata, Euapta gedeffroyi, and Holothuria atra. The validation results of the booklet receive an average score of 88%, placing it in the category of very feasible for use in school learning activities. Â This media can empower studentsâ€™ knowledge about biology topic, expecially in Echinoderm to support environmental sustainability.